Beyond the “string of beads”: case-based exploration of diagnostic pitfalls and solutions in reversible cerebral vasoconstriction syndrome - Seung Ae Kim; Eung Yeop Kim; Shuu-Jiun Wang; Mi Ji Lee (The Journal of Headache and Pain)
Abstract Background The diagnosis of reversible cerebral vasoconstriction syndrome (RCVS) is challenging due to its varied clinical manifestations and imaging findings. While it typically presents with a sudden, severe thunderclap headache and multifocal constriction of the cerebral arteries, the wide spectrum of radiological presentations may complicate the diagnosis. Main Body This review presents a series of cases that show both typical and atypical presentations of RCVS. Typical cases show the characteristic “string of beads” pattern on angiography, which usually resolves within 3–6 months. However, diagnostic challenges arise when angiography appears normal in the early stages or when imaging artifacts obscure the findings. In addition, the variability in vasoconstriction patterns and the need for a differential diagnosis further complicate the accurate identification. These cases highlight the importance of considering RCVS in patients with recurrent thunderclap headaches, even when the initial imaging is inconclusive. Recognizing these challenges and the variability in presentation, along with the use of high-resolution vessel wall MRI and blood-brain barrier imaging, can improve diagnostic accuracy and improve patient outcomes. Conclusion The diagnosis of RCVS requires careful integration of clinical evaluation and advanced imaging techniques, with particular attention to radiological findings that can guide accurate diagnosis and management. Despite challenges, such as normal early stage angiography and imaging variability, maintaining a high suspicion of RCVS is essential, especially in patients with recurrent thunderclap headaches.